Pengaruh religiusitas dan kematangan emosi terhadap kedisiplinan santri di pesantren pada masa pandemi Covid-19 - Hudha, Misbachul; Umam, Reza Wasilul (UIN Maulana Malik Ibrahim Malang, 2022)
ABSTRACTCovid 19 has brought many changes in all aspects, the education sector has become one of the aspects that are of concern. Since the beginning of covid in Indonesia, a learning system has emerged that has been carried out boldly (in the network) in both formal and Islamic education for about two years or until 2022. Where courageous learning for two years has had a significant impact, one of which is decreased discipline among Islamic boarding school students. Whereas disciplined behavior is the most important thing in life. The purpose of this study was to analyze the influence of religiosity, and emotional maturity on the discipline of Islamic boarding school students of Arrahman Malang students during the Covid-19 pandemic. This research method used a quantitative approach, the sampling technique was purposive sampling, using a sample of 36 Islamic boarding school students Arrahman Malang students.The data was analysis technique that is using multiple linear regression analysis. The results of this study indicate that the religiosity variable does not affect the discipline of students with a value coefficient of -0.011. In the emotional maturity variable, a coefficient value of 0.357 is obtained, meaning that there is a significant influence between the emotional maturity and the discipline of the students, meaning that the better the emotional maturity of the students, the better the discipline of the students, and vice versa if the emotional maturity of the students is low, the discipline of the students is also low.KEY WORDS: religiosity; emotional maturity; discipline; covid-19; islamic boarding schoolsABSTRAKCovid 19 membawa banyak perubahan dalam segala aspek, sektor pendidikanpun menjadi salah satu aspek yang menjadi perhatian. Sejak awal covid di Indonesia muncul sistem pembelajaran dilakukan dengan daring (dalam jaringan) baik pendidikan formal maupun pesantren selama kurang lebih dua tahun atau hingga tahun 2022. Dimana pembelajaran daring selama dua tahun membawa dampak yang signifikan salah satunya kedisiplinan yang menurun di kalangan santri pesantren. Padahal perilaku disiplin merupakan hal terpenting dalam kehidupan. Tujuan penelitian ini adalah menganalisis pengaruh religiusitas, kematangan emosi terhadap kedisiplinan santri pesantren mahasiswa Arrahman Malang pada masa pandemi covid 19. Metode penelitian ini ialah dengan pendekatan kuantitatif, teknik pengambilan sampel yaitu purpisive sampling, digunakan sampel sebanyak 36 santri pesantren mahasiswa Arrahman Malang, teknik analisis data yaitu menggunakan analisis regresi linier berganda. Hasil penelitian ini menunjukkan variabel religiusitas tidak berpengaruh terhadap kedisiplinan santri dengan diperoleh nilai koefisien sebesar -0.011. Pada variabel kematangan emosi mendapatkan nilai koefisien sebesar 0.357, berarti ada pengaruh yang signifikan antara kematangan emosi dengan kedisiplinan santri, artinya semakin baik kematangan emosi santri maka semakin baik pula kedisilinan santri, begitu pula sebaliknya jika kematangan emosi santri rendah maka kedisiplinan santri juga rendah.KATA KUNCI religiusitas; kematangan emosi; disiplin; Covid-19; pesantren Copyright ©2022. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0